The outcomes of using high oxygen concentration in pediatric patients - HARMAN, FERHAT; ÖZTÜRK, MAKBULE NİLÜFER; ZENGİN, SENİYYE ÜLGEN (SPRINGER HEIDELBERG, 2022)
Oxygen reserve index, available as part of Masimo Rainbow SET pulse oximetry, is a noninvasive and continuous variable intended to provide insight into a patient's oxygen status in the moderate hyperoxic range (PaO2 > 100 and <= 200 mm Hg), defined as a patient's oxygen reserve. When used in conjunction with pulse oximetry, ORi extends the knowledge on a patient's oxygen status providing clinically important information helping to prevent hyperoxemia and hypoxemia. There are limited data on patients undergoing craniosynostosis surgery. Our primary goal was to evaluate the effects of different concentrations of inspiratory oxygen (FiO(2)) on patient oxygenation status by monitoring ORi. Thirty patients scheduled for craniosynostosis were included in this observational cohort study. Patients were randomized into two equal groups: Group 1 received a fraction of inspired oxygen of 0.8 and group 2 received a FiO(2) of 0.6 during induction of anaesthesia. In addition to standard haemodynamic variables with ORi were recorded at baseline 1 min, 5 min, 60 min, and 120 min after intubation. Postoperative complications, length of stay in the intensive care unit and hospital were recorded. In total, 14 patients were evaluated in each group. Gender, age, BMI, ASA scores were similar between groups (p > 0.05). In Group 1, ORi values were significantly higher when compared to group 2 at baseline (0.86 +/- 0.21 vs 0.45 +/- 0.32, p = 0.001), one minute (0.61 +/- 0.24 vs 0.27 +/- 0.21, p = 0.001), and 5 min (0.34 +/- 0.31 vs 0.10 +/- 0.13, p = 0.033). High inspired oxygen concentration during induction of anesthesia in pediatric patients is associated with higher levels of ORi. Therefore, ORi may provide the means to safely reduce the inspired oxygen fraction during inhalational induction in paediatric patients.
Keywords: Oxygen reserve index; Hyperoxemia; Pediatric anesthesia; CRANIOSYNOSTOSIS; MORTALITY; PREOXYGENATION; RESUSCITATION; ATELECTASIS; ANESTHESIA; BENEFITS